Analyzing the Role of Great Powers in Creating the Durand Line and Its Impact on Afghanistan-Pakistan Relations - Fayaz Gul Mazloum Yar; Ihsanullah Ihsan; Mohammad Shafiq Hafiz (RIRAI Publisher, 2022)
The existence of countries based on borders is the product of the second half of the nineteenth century, and Afghanistan is the first country to be established on this basis. Afghanistan's current political borders are imposed, largely influenced by the political struggles and rivalries of the British and Tsarist Russia in the 19th century and during the Great Game to prevent a direct confrontation between the two powers in Central Asia. They set up a barrier between themselves and established the country's political borders through several treaties. Meanwhile, the Durand Line and the issue of Pashtunistan are very important, because the developments in Afghanistan after the signing of the Durand Line entered a new phase, and with the passage of time and some major changes such as Britain's withdrawal from the subcontinent and India's independence, not only failed, but the advent of Pakistan and the conflict of interests between the two neighboring countries has led to the complexity of events which has been on the rise and continues to this day. The present study, using descriptive-analytical methods and citing reliable library sources, seeks to examine the role of major powers such as Britain and Russia in shaping Afghanistan's political borders, especially the Durand Line, and its negative consequences for Afghanistan and its role in creating differences between Afghanistan and Pakistan. The results show that regional and supra-regional powers, especially Britain, played a role in shaping Afghanistan's borders, and Durand's mystery is one of the leftovers of British-Indian colonialism, which has now become a source of discord between Afghanistan and Pakistan and its negative consequences to Afghanistan includes land closures and lack of access to open waters, support and rise of political instability in Afghanistan